2012
DOI: 10.1371/journal.pone.0052334
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Tuberculosis Treatment among Migrant Pulmonary Tuberculosis Patients in Shandong, China: A Quantitative Survey Study

Abstract: Adherence to TB treatment is the most important requirement for efficient TB control. Migrant TB patients’ “migratory” nature affects the adherence negatively, which presents an important barrier for National TB Control Program in China. Therefore, TB control among migrants is of high importance.The aim of this study is to describe adherence to TB treatment among migrant TB patients and to identify factors associated with adherence. A total of 12 counties/districts of Shandong Province, China were selected as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
46
3
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 8 publications
(10 reference statements)
7
46
3
3
Order By: Relevance
“…However, some studies have shown an association between non-adherence and gender of the patients [9,13]. Some studies indicated that educational status [8,14] and marital status [15] were associated with anti-TB medication adherence unlike this study.…”
Section: Characteristics N (%) Non-adherence N (%) Aor (95% Ci) ¶ P contrasting
confidence: 65%
“…However, some studies have shown an association between non-adherence and gender of the patients [9,13]. Some studies indicated that educational status [8,14] and marital status [15] were associated with anti-TB medication adherence unlike this study.…”
Section: Characteristics N (%) Non-adherence N (%) Aor (95% Ci) ¶ P contrasting
confidence: 65%
“…Compared with urban residents, rural-to-urban migrant workers are often lack of medical insurance and are in a disadvantage position in access to health care because of the low income. In Zhou's study, 65% of the migrant TB patients in Shanghai did not have any kind of health insurance 13 and in another study among migrants population in East China, only 6.5% of new pulmonary tuberculosis cases had medical insurance. 4 The situation is worse as the cost of medical care has risen dramatically in recent years.…”
Section: Introductionmentioning
confidence: 90%
“…This shows that supervised first dose of the week motivates the patients and imparts the importance of compliance to the regimen even in the continuation phase. Similar studies conducted in China, 18 Malaysia, 19 and Nepal 20 showed that when the treatments were supervised as per the guidelines of DOTS it significantly increased the treatment adherence. Hence it is of great importance to advocate the supervised therapy among the patients to improve treatment outcome.…”
Section: Discussionmentioning
confidence: 68%